The Role of Islamic Law in Promoting Inclusive and Quality Education to Achieve the SDGs 2030 - Karimuddin Abdullah Lawang; Iskandar (JKA, 2025)
Islamic law plays a significant role in promoting inclusive and quality education, which is essential for achieving the Sustainable Development Goals (SDGs) 2030. Through its principles, Islamic law ensures the right of every individual to receive fair and equitable education while encouraging the participation of all societal groups, particularly marginalized communities. This research examines various approaches taken by Muslim-majority countries in implementing Islamic law within their educational systems. By integrating Islamic ethical and moral values, education can enhance the quality of learning and shape student character. The findings indicate that the application of Islamic law in education not only improves access and equity but also contributes to achieving quality education goals aligned with the SDGs.